Competitive Indices and Production of Maize (Zea mays L.) and Cowpea (Vigna unguiculata) Intercropping System as Influence by Nutrient Management Practices - Chhetri, Binoy; Sinha, A. C. (International Journal of Bio-resource and Stress Management, 2019)
A field experiment was conducted at Instructional Farm of UBKV, Pundibari, Cooch Behar, West Bengal during 2013 and 2014. To evaluate the yield attributes, yield and competition function of maize (Zea mays L.) and cowpea (Vigna unguiculata) intercropping system. The grain yield, stover yield and harvest index of maize were significantly higher in case of pure stand of maize than intercropping systems. Among the integrated nutrient management practices, treatment supplied 75% RDF+PSB+Azotobacter+vermicompost @ 5.0 t ha-1 produced highest seed yield, stover yield, harvest index and yield attributes. The values of seed yield (938 and 943 kg ha-1), stem yield (1421 and 1435 kg ha-1), harvest index of cowpea (40.09 and 39.97%) and yield attributes was significantly higher in sole crop. Among the integrated nutrient management practices, treatment supplied with 75% RDF+PSB+Azotobacter+vermicompost @ 5.0 t ha-1 produced highest seed yield (833 and 837 kg ha-1), stem yield (1349 and 1358 kg ha-1), harvest index (38.50 and 38.54%) and yield attributes. Maize equivalent yield, competition ratio, LER, RCC, competition index, aggressivity, ATER, LEC and monetary advantage was found to be higher with 2:2 row ratio combinations. Integrated nutrient management practices, maize equivalent yield, competition ratio, LER, RCC, competition index, aggressivity, ATER, LEC and monetary advantage found to be higher under 75% RDF+PSB+Azotobacter+vermicompost @ 5.0 t ha-1. It may be concluded that maize grown as intercrop with cowpea in 2:2 row ratio combinations and supplied with 75% RDF+PSB+Azotobacter+vermicompost @ 5.0 t ha-1 (N3) is best for obtaining overall gain.